Ensino de língua estrangeira na educação infantil: um estudo sobre a fala institucional de sala de aula - Araujo, Luciana Gossmann (Universidade do Vale do Rio do Sinos, 2009)
This study seeks to investigate the role of using the Initiation – Response – Evaluation & Initiation – Response – Follow up sequences (hereafter IRE & IRF), as well as the role of puppets in fostering the use of the target language and the development of new identities in the second language classroom researched. In order to do so, principles and procedures of action-research, and therefore, from qualitative methodology of analysis were adopted. The researcher-teacher applied, in her classroom, didactic material that she had elaborated in a previous study. The classes of English recorded for the present study took place in a kindergarten class of a private school located in Vale do Rio dos Sinos. The recordings, which occurred once a week, during three months and a half, were made in a class composed by 20 students, of whom 10 were boys and 10 were girls. In a preliminary analysis, the recordings seemed to disclose a great deal of IRE sequences in the interactions. However, upon closer inspection, the analys
Keywords: andaimento; discurso - sala de aula; fantoches; IRA & IRF; ensino - língua estrangeira - crianças; classroom discourse; puppets; scaffolding; teaching foreign language to children; Lingüística